2022
DOI: 10.3389/feduc.2022.827496
|View full text |Cite
|
Sign up to set email alerts
|

“A Common Obsession”: Children’s and Young People’s Perceptions of Learning in an Intensive Summer Choral Program

Abstract: This article reports the findings of an investigation of children’s and young people’s perceptions of learning and life outcomes, environmental supports and teaching and learning strategies encountered in an intensive summer choral program. Whilst the recognition of children’s and young people’s right to voice their perspectives was enshrined in the UN Convention on the rights of the child (1989), the music education profession has taken some time to foreground children’s and young people’s voice as a research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Few highly successful children’s choirs have been investigated by research (e.g., Barrett & Zhukov, 2022; Bartolome, 2013). Gondwana Sydney Children’s Choir has earned a reputation as the most respected and celebrated Australian vocal program for school-age singers since it was created more the 30 years ago.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Few highly successful children’s choirs have been investigated by research (e.g., Barrett & Zhukov, 2022; Bartolome, 2013). Gondwana Sydney Children’s Choir has earned a reputation as the most respected and celebrated Australian vocal program for school-age singers since it was created more the 30 years ago.…”
Section: Methodsmentioning
confidence: 99%
“…Choral singing research has demonstrated positive impacts on the well-being and health of choristers (Barrett & Zhukov, 2022;Clift et al, 2016;Clift & Hancox, 2010;Fernández-Herranz et al, 2021;Lynch & Wilson, 2018;Orton & Pitts, 2019;Parker, 2014;Stewart & Lonsdale, 2016;Zhukov et al, 2021). The benefits of choral singing for adults reported in a large multinational survey included "positive affect, focused attention, deep breathing, social support, cognitive stimulation and regular commitment" (Clift & Hancox, 2010, p. 80).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leadership is another skill that is improved through music, mainly through participation in choral ensembles [39], through participation in instrumental ensembles [17,42], through musical and didactic activities at the preschool level [15,37] (or through the teaching of musical language [56]. In this regard, not only do participants in educational interventions benefit, but music teachers' leadership skills and responsibilities as managers of musical activities are also enhanced [24,35,38,58].…”
Section: Social Skillsmentioning
confidence: 99%
“…Authors such as Kang [50] claim that participation in musical ensembles increases wellbeing, while others argue that it is the music itself that increases participants' perceptions of well-being [12,39,44,45,49,52,54,57].…”
Section: Social Skillsmentioning
confidence: 99%